2023
DOI: 10.1021/acsami.3c01704
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity with Graphitization in Ti-Doped DLC/Steel Tribopair: Response on Humidity and Temperature

Abstract: The anti-friction of diamond-like carbon (DLC) is achieved by a well-developed carbonaceous transfer layer, and Ti-doped DLC is developed into a robustly built-up carbonaceous transfer layer. The friction performance of DLC depends on the operating environment, e.g., ambient gas, humidity, temperature, lubricants, and mating material. In this study, we aimed to reveal the environmental sensitivities of Ti-DLC on friction characteristics. To this end, a Ti-DLC was rubbed against a steel ball, and friction behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…This transition has been discussed as the main reason for the excellent frictional properties of DLC. 56,57 Figure S5 shows the evolution of sp 3 to sp 2 ratio in our multilayer coatings, demonstrating a weak dependence of DLC bond transition as a function of bilayer thickness. This observation suggests that the variation of scratch hardness can be mainly associated with the thickness of the WC layers rather than DLC ones.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…This transition has been discussed as the main reason for the excellent frictional properties of DLC. 56,57 Figure S5 shows the evolution of sp 3 to sp 2 ratio in our multilayer coatings, demonstrating a weak dependence of DLC bond transition as a function of bilayer thickness. This observation suggests that the variation of scratch hardness can be mainly associated with the thickness of the WC layers rather than DLC ones.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Environmental Adaptability: How a material responds to changes in its environment is key to its potential for superlubricity. A study conducted by Kim et al [ 19 ] demonstrated that the friction between Ti-doped DLC and steel surfaces could transition to superlubricity under specific humidity and temperature conditions. The researchers discovered that the increased presence of water molecules in a humid environment could form a lubricating layer between the surfaces, significantly reducing friction.…”
Section: Materials Science In Superlubricitymentioning
confidence: 99%
“…Thus, precise control and consideration of these environmental parameters are necessary for achieving and maintaining the desired superlubric behavior in practical applications. For example, Kim et al [ 19 ] highlighted how superlubricity in titanium-doped diamond-like carbon on a steel tribopair could be accomplished under specific humidity and temperature settings. To achieve a superlubric sliding regime, numerous solutions focus on mitigating frictional energy dissipation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Superlubricants can be broadly classified into two categories: solid and liquid . For the former, typical ones include molybdenum disulfide, graphene, diamond-like carbon films, and multiwalled carbon nanotubes. However, solid superlubricity materials usually require specific conditions (e.g., vacuum/inert gas atmosphere, incommensurate contact, micrometer size, and absolute surface rigidity) to achieve superlubricity, whereas the liquid ones easily achieve macroscopic superlubricity on routinely flat surfaces under atmospheric conditions such as aqueous phosphoric acid solutions . As a result, liquid superlubricants have a much greater potential than solid superlubricants to meet the real-world requirements of a wide range of applications and are compatible with most existing lubrication systems.…”
Section: Introductionmentioning
confidence: 99%